Investigation of the bioconversion of constituents of olive effluents for the production of valuable chemical compounds - Notshe, Thandiwe Loretta (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2002)
Olive mill wastewater is produced in large quantities during the production of olive oil and olive production effluents are produced during the processing of olives. This project was planned to find a use for constituents found in olive production wastewater. The task was carried out by first characterizing the olive effluents, then screening microorganisms for growth in the effluents and reduction of the pollutant properties of the effluents. An investigation into the biotransformation of aromatic compounds present in the effluents into useful chemicals, was carried out. The olive production effluents were collected from different stages in the process for treating olive wastewater, viz, a fermentation tank (FB), the surface of a digester (LV) and an evaporation pond (SO). The three effluents were characterized by investigating their phenolic composition. Protocatechuic acid, vanillic acid, syringic acid, hydroxyphenyl acetic acid, coumaric acid and ferulic acid were identified in an olive effluent, FB, using thin layer chromatography (TLC) and High perfomance liquid chromatography (HPLC). Hydroxyphenyl acetic acid constitutes almost 60% of the organics in olive effluent FB. Five bacteria, namely RU-LV1; RU-FBI and RU-FB2; RU-SOI and RU-S02, were isolated from the olive effluents LV, FB and SO respectively. These isolates were found to be halotolerant and were able to grow over a broad temperature and pH range, with the maximum temperature and pH for growth being 28Â°C and pH 7 respectively. A range of microorganisms were evaluated for their ability to grow and reduce the total phenolic content of the olive effluents. Among these Neurospora crassa showed the highest potential for the biological reduction of total phenolics in olive effluents. Approximately 70% of the total phenolic content was removed by N. crassa. Trametes verscilor, Pseudomonas putida strains, RU-KMI and RU-KM3s, and the bacteria isolated from olive effluents could also degrade the total phenolic content of olive effluents, but to a lesser extent. The ability of the five bacterial isolates to grow and degrade aromatic compounds was assessed by growing them in medium with standard aromatic compounds. RU-L V1 degraded 96%, 100%, 73% and 100% of caffeic acid, protocatechuic acid, p-coumaric acid and vanillic acid respectively. The other isolates degraded caffeic acid and protocatechuic acid, but their ability to degraded p-coumaric acid and vanillic acid was found to be lesser than the ability of RU-LV1 to degrade the same aromatic compounds. Whole cells of RU-LV1 degraded vanillic acid but no metabolic products were observed on HPLC analysis. Resting cells, French pressed extract, cell free extracts and cell debris from RU-LV1 cells induced with vanillic acid degraded vanillic acid, ferulic acid and vanillin at rates higher than those obtained from non-induced cultures. No products were observed during the degradation of vanillic acid. Ferulic acid was converted into vanillic acid by French pressed extract, cell free extract and cell debris of RU-LV1. The maximum yield of vanillic acid as a product (0 .23 mM, 50 %yield) was obtained when cell free extracts of RU-LVI, grown in glucose and induced by vanillic acid, were used for the degradation of 0.4 mM ferulic acid. Vanillin was rapidly converted into vanillic acid by resting cells, cell free extracts and French pressed extract of RU-LVI. Using molecular techniques, the similarity ranking of the RU-LVI 16S rRNA gene and its clone showed a high similarity to Corynebacterium glutamicum and Corynebacterium acedopltilum. The rapid degradation of vanillin to vanillic acid suggests that extracts from RU-LV1 degrade ferulic acid into vanillin which is immediately oxidized to vanillic acid. Vanillic acid is also considered as a high value chemical. This project has a potential of producing useful chemicals from cheap substrates that can be found in olive effluents.,KMBT_363
Keywords: Phenols; Sewage -- Purification; Effluent quality